Xerostomia and polypharmacy among dependent older New Zealanders: a national survey. (23rd July 2020) - Thomson, William Murray; Ferguson, Catherine Anna; Janssens, Barbara E; Kerse, Ngaire M; Ting, Graeme S; Smith, Moira B
Abstract: Background: Medication-induced xerostomia is common in older people. We investigated medication use and xerostomia in dependent older New Zealanders. Methods: Medication and xerostomia data analysed from a nationally representative survey of dependent older people. Automatic interaction detection analysis identified medications combinations most strongly associated with xerostomia, and then xerostomia was modelled. Results: Just over half were taking five to nine different medications; one in five was taking 10+. Xerostomia prevalence (29.4%; 95% confidence interval 26.5, 32.5) was higher among the latter and lowest in psychogeriatric patients. After controlling for age and sex, it was higher among people taking any antidepressant, and higher still with a tricyclic antidepressant and either a steroid or an anticholinergic, or among people taking a bronchodilator without prophylactic aspirin. Conclusions: Health practitioners should work together to ensure that those with xerostomia are managed in a timely and appropriate manner. Medication review is an important component of that.